PEMBELAJARAN PRAKTIKUM EKOLOGI TUMBUHAN DENGAN METODE RISET MINI DENGAN MEMANFAATKAN TUTOR SEBAYA - Amprasto, Mr; Supriatno, Bambang; Safaria, Tina (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2005)
The result of evaluation on the Plant Ecology for student of Biological education was still low. It indicated that the learning process of this subject was not efective enough. Therefore, it has to be though, how to conduct this learning process of Plant Ecology learning effectively. The first step of Plant Ecology learning was selecting some student to be peer tuturs, then giving them instruction the practical exercise was carrying out by using peer tutors on learning concepts of each the practical topics. The method of practical exercise was small research, designing each topic of practical exercise as simple research. This method was expected to optimize the student ability. The study reavealed that the learning in practical exercise with peer tutor increasing the result of evaluation. It is shown that average of final test was 69.96 higher than primary test (48.8). The increasing result of evaluation is conducted with student motivation, whole activities of teacher and students. Peer tutors can be played as catalysator, dinamysator and motivator on groupe; small research made the learning process more interested, so the learning became more effectively.Keywords: Plant Ecology, small research Method, Field work,peer tuturs